Morphological and Anatomical Characteristics of Herbaceous Plant Leaves in Different Light Intensities in Education Forest of Forestry Faculty of Mulawarman University - Karyati, Jhen Rio R, Muhammad S . (Universitas 17 Agustus 1945 Samarinda, 2017)
This study objective was to know the morphological and anatomical characteristics of dominant herbaceous plant leaves in different light intensities. Three selected study sites represented heavy, moderate, and few light intensities. The vegetation survey was done for all herbaceous plants in 10 quadrants of 2 m × 2 m in three research locations. The analysis on morphological and anatomical characteristics was done for leaves of five dominant species in the study sites. The morphological characteristics of herbaceous plant leaves in heavy, moderate, and few light intensity were for leaf length 22.1; 25.5; 20.0 cm and leaf wide 6.0; 5.8; 5.0 cm. The anatomical characteristics of herbaceous plant leaves in heavy light intensity were average number of chlorophyll 44.5; stomata length 32.60 µm, and stomata wide 25.84 µm; in moderate light intensity were average number of chlorophyll 51.6; stomata length of 27.79 µm, and stomata wide 24.36 µm; and in few light intensity were average number of chlorophyll 49.1; stomata length 28.36; and stomata wide 23.82 µm